Pengaruh Brand Image, Content Marketing Dan Electronic Word Of Mouth (E-WOM) Terhadap Purchase Decision Pada Produk Skincare Ms Glow (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Rana, Dhifah Tsabitah; Priyono, Achmad Agus; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the effect of Brand Image, Content Marketing, and Electronic Word of Mouth (E-WOM) on Purchase Decision on MS Glow Skincare products. This type of research is quantitative with an explanatory research approach. The population in this study who have purchased MS Glow Skincare products at least once in the Islamic University of Malang environment. The sampling technique used Snowball Sampling with a sample of 85 respondents. Data obtained from a questionnaire using a Likert scale. The results of this study indicate that Brand Image, Content Marketing, and Electronic Word of Mouth (E-WOM) simultaneously affect Purchasing Decisions. Partially Brand Image, Content Marketing, and Electronic Word of Mouth (E-WOM) have an effect on Purchasing Decisions. Keywords: Purchase Decision, Brand Image, Content Marketing, Electronic Word Of Mouth (E-WOM)